Surgical removal of the lens with vitrectomy in patients with nanophthalmos and glaucoma - Kamińska, Anna; Sołtysiuk, Magdalena; Romaniak, Agnieszka; Szaflik, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Nanophthalmos is a rare eye developmental disorder associated with anatomical and ultrastructural abnormalities that predispose to specific comorbidities including secondary angle-closure glaucoma that frequently proves recalcitrant to treatment. These abnormalities might increase the rate of complications associated with intraocular surgery. This paper discusses pathomechanisms that underlie the development of such complications. The outcomes of phacoemulsification combined with pars plana limited vitrectomy are also presented. This surgical modality allows safe and minimally invasive cataract extraction in small eyes with extremely shallow anterior chamber and elevated intraocular pressure. The benefit is not only vision improvement, but also glaucoma treatment due to elimination of anatomical conditions that contribute to angle closure. This may require extraction of a clear lens.